Liberalismo e tradição inquisitória : genealogia do sistema processual penal no Brasil Imperial - Poli, Camilin Marcie de (2022)
This study examines how did the construction of Imperial Brazil’s criminal procedure structure develop. One will verify the political positioning that prevailed during the elaboration of the 1832 Criminal Procedure Code and the political positioning that built the path to the 1841 reform. One analyzes the influence of political liberalism in the Brazilian context, from the transition between the Old Regime to Modernity, as well as the insertion of liberal principles in the 1824 Imperial Constitution, in order to acknowledge its influence in the formation of Brazilian criminal procedure. In addition, one seeks to look at either the ruptures and the continuities between the old and the new procedure model, examining to what extent the permanency of inquisitorial tradition in the legal imaginary of political actors prevented the systematization of an accusatory criminal procedure, leading to the institutionalization of inquisitorial liberalism.